Analisa Jaringan Sosial Pedagang Bubuk Kopi Gampong Ie Masen Ulee Kareng - Munandar,; Bukhari Yusuf,; Ibnu Phonna Nurdin,; Khairulyadi,; Firdaus Mirza Nusuary, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Ulee Kareng District is the largest coffee powder producing area in Aceh. This success cannot be separated from the social network formed by coffee traders and consumers. This study aims to analyze the social network that occurs in Ulee Kareng coffee powder traders, namely Solong Coffee Powder, Said Ida Coffee Powder, and Kupi Ceeh23. This study was conducted in Ulee Kareng District and has a qualitative approach. Data collection techniques through observation, interviews and documentation. Furthermore, the data will be analyzed from data reduction, data presentation to drawing conclusions. The results of the study show that the social network that is formed is very good including 4 things, namely: 1. Strong network norms and density, 2. Strong ties and weak ties run continuously to help open new networks, 3. The role of active structural holes, and 4. The anchorage of non-economic actions to economic actions runs sustainably. Therefore, it can be concluded that the social network that has been formed in coffee traders in Ulee Kareng District is very good. Indirectly, this shows that there is very good social network management by coffee traders. It is hoped that the social network formed among these coffee traders can be an example for other coffee traders and the government to provide empowerment for coffee traders who do not yet have a social network like the network formed among coffee traders in Ulee Kareng District.